Corrigendum to “Effects of pretreatment applied to sugarcane bagasse on composition and morphology of cellulosic fractions” [Biomass Bioenergy 126 (2019) 231–238] - Laluce, Cecilia [UNESP]; Roldan, Ismael U. [UNESP]; Pecoraro, Edison [UNESP]; Igbojionu, Longinus I. [UNESP]; Ribeiro, Clovis A. [UNESP] (Elsevier, 2020)
Following a review of author contributions with all parties the author list has been augmented to include Dr. Daniel Pasquini, (Chemistry Institute, Federal University of Uberlândia-UFU, Av. João Naves de Ávila, 2121, Bloco 1D, Campus Santa Mônica, CEP 38400-902, Uberlândia, Minas Gerais, Brazil). The authors would like to apologise for any inconvenience caused.
Corrigendum to “Effects of pretreatment applied to sugarcane bagasse on composition and morphology of cellulosic fractions” [Biomass Bioenergy 126 (2019) 231–238] (Biomass and Bioenergy (2019) 126 (231–238), (S096195341930090X), (10.1016/j.biombioe.2019.03.002))